2014
DOI: 10.3109/00365548.2014.898333
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and treatment of HIV-1 infection in pregnancy: Swedish recommendations 2013

Abstract: Prophylaxis and treatment with antiretroviral drugs and elective caesarean section delivery have resulted in very low mother-to-child transmission of HIV during recent years. Updated general treatment guidelines and increasing knowledge about mother-to-child transmission have necessitated regular revisions of the recommendations for the prophylaxis and treatment of HIV-1 infection in pregnancy. The Swedish Reference Group for Antiviral Therapy (RAV) updated the recommendations from 2010 at an expert meeting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The introduction of new antiretroviral agents probably contributed to this decrease since we found a correlation between the drop in reported side effects and alterations in the prescribed third agent in ART during the time period. The changes in ART prescription, recommended by the Swedish HIV treatment guidelines [18][19][20] and also presented in a previous study [23], were characterized by the decline in prescription of EFV and PI and the increased prescription of integrase inhibitors as third agents.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The introduction of new antiretroviral agents probably contributed to this decrease since we found a correlation between the drop in reported side effects and alterations in the prescribed third agent in ART during the time period. The changes in ART prescription, recommended by the Swedish HIV treatment guidelines [18][19][20] and also presented in a previous study [23], were characterized by the decline in prescription of EFV and PI and the increased prescription of integrase inhibitors as third agents.…”
Section: Discussionmentioning
confidence: 71%
“…Fifteen of these also provided data through individual qualitative interviews. During the data collection period, PLWH received ART according to the Swedish HIV treatment guidelines; these were updated in 2009 [18], 2013 [19] and 2016 [20].…”
Section: Study Populationmentioning
confidence: 99%
“…While as early as 1998, De Ruiter suggested that WLWH “may benefit from the administration of bromocriptine or cabergoline” , there is no discussion of lactation inhibition in the US , the Australian or the World Health Organization guidelines . The 2014 and the 2017 Swedish guidelines suggest that “The woman should be provided support to interrupt the milk production” but no specific measure is suggested . The 2008 British guidelines suggested for the first time the use of cabergoline .…”
Section: Resultsmentioning
confidence: 99%
“…The main eligibility criterion was represented by undetectable HIV-RNA plasma viral load (< 50 copies/ml in 2012). This approach is common to most national guidelines from European countries, while other European (France, Sweden, Denmark and Holland) and non-European countries (Canada, US) have selected a less stringent approach, considering eligible for vaginal delivery also women with low-level detectable HIV-RNA (usually no more than 150-1000 copies/ml, according to the individual national guidelines) [2][3][4][5][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%